Conceptualizing the challenges and success factors to born global startups - Rother, Diarra (2020)
Since the 1970’s a growing number of companies appear to internationalize at inception or shortly after. As international markets gradually interconnect, smaller and younger businesses are also becoming more global. Early internationalization of startups is often perceived as having a vast number of obstacles. In fact, however, all challenges connected to early internationalization can be tackled with specific success factors. While previous research typically focuses on the reasons why BGs have emerged, this thesis focuses on strategies of overcoming challenges connected to early internationalization. To illustrate this further, a framework was developed.